Two-Partner Secretion: Combining Efficiency and Simplicity in the Secretion of Large Proteins for Bacteria-Host and Bacteria-Bacteria Interactions - Guérin, Jeremy; Bigot, Sarah; Schneider, Robert; Buchanan, Susan K.; Jacob-Dubuisson, Françoise (Frontiers in Cellular and Infection Microbiology, 2017)
Initially identified in pathogenic Gram-negative bacteria, the two-partner secretion (TPS) pathway, also known as Type Vb secretion, mediates the translocation across the outer membrane of large effector proteins involved in interactions between these pathogens and their hosts. More recently, distinct TPS systems have been shown to secrete toxic effector domains that participate in inter-bacterial competition or cooperation. The effects of these systems are based on kin vs. non-kin molecular recognition mediated by specific immunity proteins. With these new toxin-antitoxin systems, the range of TPS effector functions has thus been extended from cytolysis, adhesion, and iron acquisition, to genome maintenance, inter-bacterial killing and inter-bacterial signaling. Basically, a TPS system is made up of two proteins, the secreted TpsA effector protein and its TpsB partner transporter, with possible additional factors such as immunity proteins for protection against cognate toxic effectors. Structural studies have indicated that TpsA proteins mainly form elongated β helices that may be followed by specific functional domains. TpsB proteins belong to the Omp85 superfamily. Open questions remain on the mechanism of protein secretion in the absence of ATP or an electrochemical gradient across the outer membrane. The remarkable dynamics of the TpsB transporters and the progressive folding of their TpsA partners at the bacterial surface in the course of translocation are thought to be key elements driving the secretion process.